2020
DOI: 10.3897/rrpharmacology.6.50373
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet activity of new derivatives of benzimidazole containing sterically hindered phenolic group in their structure

Abstract: Citation: Spasov AA, Kucheryavenko AF, Gaidukova KA, Kosolapov VA, Zhukovskaya ON (2020) Antiplatelet activity of new derivatives of benzimidazole containing sterically hindered phenolic group in their structure. Research Results in Pharmacology 6(1): 1-9. https://doi. AbstractIntroduction: Cardiovascular diseases are currently the leading cause of global disability and mortality. According to the centers for disease control and prevention, the average life expectancy of a person would be 10 years longer but f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…[1,5,6] Copper is an essential element responsible for the function of many cellular enzymes, such as cytochrome c oxidase, NADH dehydrogenase 2, tyrosinases and proteins. [7,8] The previous studies [9,10] revealed particularly high antioxidant and antiaggregant properties of benzimidazole derivatives containing spa-tially hindered phenol moieties efficiently inhibiting oxidative stress. Metal coordination changes the redox potential and additionally affects its antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,5,6] Copper is an essential element responsible for the function of many cellular enzymes, such as cytochrome c oxidase, NADH dehydrogenase 2, tyrosinases and proteins. [7,8] The previous studies [9,10] revealed particularly high antioxidant and antiaggregant properties of benzimidazole derivatives containing spa-tially hindered phenol moieties efficiently inhibiting oxidative stress. Metal coordination changes the redox potential and additionally affects its antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…As the appropriate ligands bearing 2,6di-tert-butylphenol pendants we have chosen 2,6-di-tert-butyl-4-(2-(2-hydroxyphenyl)-1H-benzo [d]imidazol-1-yl)phenols 3 known to exhibit pronounced antioxidant and antiplatelet activities. [9,10] The compounds were synthesized in good yields by the reaction of quinone imines 1 with various derivatives of salicylic aldehyde (Scheme 1) in general accordance with the procedures described for some of the previously obtained compounds of this group. [12][13][14][15][16][17] The structures of the newly prepared compounds (1 b-e, 3 b-e) were established on the basis of the data of IR-, massand 1 H NMR spectroscopy and elemental analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its inhibitory effect might be attributed to the presence of 1-imidazolyl moiety at one end carrying a long chain of three sugar moieties. A series of benzimidazole derivatives bearing a sterically hindered phenolic group in their structures were evaluated for in vitro antiplatelet activity using the Adenosine diphosphate (ADP)-induced platelet aggregation model of rabbit’s plasma ( Spasov et al, 2020 ). Compound 528 showed notable antiplatelet activity by exceeding the standard acetylsalicylic acid by 21.8 times.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…В ходе ранее проведенных исследований, среди гетероциклических соединений были выявлены вещества, проявляющие антиагрегантные и антиоксидантные свойства [11][12][13]. Соединение под шифром РУ-1144 (1-(2,6-дитретбутил-4-(1-гидроксиэтил)-фенил-пиримидобензимидазолгидрохлорид), способно ингибировать процессы агрегации тромбоцитов и перекисного окисления липидов, превосходя препараты сравнения ацетилсалициловую кислоту, клопидогрел и этилметилгидроксипиридина сукцинат [31]. Существуют различные методы исследования данных видов активности [15,16].…”
Section: Introductionunclassified